Endospore-forming soil bacteria - Logan, Niall A.; De Vos, Paul (Soil biology, 2011)
Aerobic endospore-forming bacteria are found in soils of all kinds, ranging from acid to alkaline, hot to cold, and fertile to desert. It is well known that endospores confer special properties upon their owners and play dominant parts in their life cycles and dispersal, and much has been written about the spores, genetics, and economic importance of these organisms. Much has also been written about soil ecology, but there is a relative dearth of literature that brings together different aspects of the behaviour and characters of endospore-formers with their contributions to soil ecosystems. This Soil Biology volume fills that gap. Following chapters that describe the current classification of these organisms, that review methods for their detection and for studying their life cycles in soils, and that examine their dispersal, other chapters show that they are active and dynamic members of soil floras that interact widely with other soil inhabitants, with roles in nitrogen fixation, denitrification, and soil remediation.